Pengenalan Penggunaan Aplikasi “ACOV19” Sebagai Activity Tracking dan Media Literasi Digital di Kelurahan Tanjungmas - Edi Jaya Kusuma; Sri Handayani; Ririn Nurmandhani (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2022)
Dian Nuswantoro University in particular the Faculty of Health has developed an application whose main focus is activity tracking and digital media literacy for users named ACOV19. The use of activity tracking applications in the pandemic era is expected to be able to ease the work of the government and read the data transaction process. However, some people still do not understand the importance of this. In addition, socializing the use of applications that are still less popular makes these applications less popular. The purpose of this service is to provide an understanding of literacy and the use of the "ACOV19" application as an activity tracker and digital media literacy to the community in order to minimize the difficulties of using the application in the Tanjung Mas community. The indicator of success in this service is that the community can understand information literacy and be able to use ACOV19. This service activity went smoothly and was attended by 15 members of KWT Tunas Bahagia who were active and enthusiastic in participating in the service. In this activity, members of the Tunas Bahagia KWT were given material presentations related to the Covid-19 tracking application, Covid-19 transmission points, and self-isolation protocols. After the presentation of the material, it was continued with the introduction and use of the ACOV-19 application. With a good level of understanding, it is hoped that Tunas Bahagia KWT members can take advantage of the ACOV19 application in their daily activities as a tracker application for the prevention of Covid-19.